[PP.29.22] WEBER SYNDROME – A CASE REPORT. (September 2017) - Gomes, D.; Alves, S.; Rodrigues, C.; Gomes, R.; Tavares, S.
Abstract : Objective: Occlusion of the arteries of the vertebro-basilar system is associated with a high morbidity and mortality, over 85% of all cases. Lesions of the smaller vessels lead to minor changes depending on their type and location, correlating with an overall better prognosis. Design and method: Case Report Results: Female, 66 years of age, Caucasian, currently treated with a Statin drug for her hypercholesterolemia. She referred sudden dizziness and loss of balance associated with nausea and vomiting. On physical examination, she presented paralysis of the III cranial nerve on the left with diplopia, left-sided conjugated nystagmus and grade 3 brachio-facial partial paralysis on the right. Cranial CT scan upon admission was negative for acute vascular lesions. Supporting bloodwork did not present any significant changes. A second follow-up cranial CT scan confirmed a normal scan. A cranial MRI demonstrated 2 millimetric hyper-signals in the medulla, right pons and median pons, interpreted as insipient ischemic vascular lesions. She had a favorable hospital stay with reasonable improvement of her overall condition. Conclusions: Vascular lesions of the posterior cerebral circulatory system can prove to be a diagnostic challenge for the skilled clinician. In this case, the clinical presentation with the persistence of neurological defects was central in the orientation of this patient and in the additional investigation performed on this patient despite the negative results on the original exams.